Multidirectional activity of bakuchiol against cellular mechanisms of facial ageing ‐ Experimental evidence for a holistic treatment approach. (9th June 2022) - Bluemke, Anika; Ring, Annika P.; Immeyer, Jeannine; Hoff, Anke; Eisenberg, Tanya; Gerwat, Wolfram; Meyer, Franziska; Breitkreutz, Sabrina; Klinger, Lina M.; Brandner, Johanna M.; Sandig, Grit; Seifert, Marietta; et al.
Abstract: Objective: Skin ageing is a multifactorial process involving formation of reactive oxygen species, consecutive inflammation with reduced epidermal and dermal cell viability and resulting damage to the extracellular matrix. Effective dermocosmetic treatment modalities should ideally address these hallmarks in a holistic approach. Here, we determined the corresponding activity profile of bakuchiol, a plant‐derived meroterpene, in an array of in vitro, ex vivo and in vivo studies and compared it to retinol, currently considered as gold standard in topical antiageing cosmetics. Methods: The antioxidative capacity and power of bakuchiol and retinol were analysed by measuring 2, 2′‐diphenyl‐1‐picrylhydrazyl (DPPH) reduction via its absorption decay and electron spin resonance spectroscopy, respectively. Effects on prostaglandin E2 (PGE2), macrophage migration inhibitory factor (MIF), fibroblast growth factor 7 (FGF7), collagen type I and VII (COL1A1, COL7A1), fibronectin (FN) levels as well as the metabolization of water‐soluble tetrazolium 1 (WST‐1) were determined in human dermal fibroblasts. Epidermal regeneration was assessed utilizing an in vitro wound healing model. FN protein levels were analysed ex vivo after treatment with a formulation containing bakuchiol, retinol or vehicle using suction blister fluid. Skin condition improvement was determined in vivo in a split‐face comparison study after application of bakuchiol or vehicle. Results: In contrast to retinol, bakuchiol demonstrated high antioxidative efficacy. Levels of PGE2 and MIF were significantly decreased by both bakuchiol and retinol. Bakuchiol but not retinol significantly increased FGF7 protein levels. WST‐1 metabolization levels were significantly augmented by bakuchiol and retinol. Bakuchiol and retinol application led to a significant augmentation of COL1A1, COL7A1 and FN protein levels. Wounds supplemented with bakuchiol but not retinol displayed a significant increase in epidermis regeneration. Clinically, areas treated with a bakuchiol‐containing formulation showed a statistically significant increase in FN protein values after a 4‐week application compared to untreated areas and areas treated with vehicle. Conclusion: These data provide evidence for the multidirectional efficacy of bakuchiol against cellular hallmarks of skin ageing. Its activity profile shares some common features with retinol but demonstrates several hitherto unknown biopositive effects in our studies, namely stimulation of the critical extracellular matrix component FN, and accelerated epidermal regeneration and wound healing. Abstract : In our study, we investigated the multidirectional effects of bakuchiol, a meroterpene isolated from the seeds of the plant Psoralea corylifolia, on cutaneous ageing. Bakuchiol exerted a broad range of antiageing effects as it acted (i) antioxidative (ii) anti‐inflammatory, increased (iii) cell activity, the expression of critical (iv) ECM components and improved (v) epidermal regeneration. These data demonstrate a multidirectional activity of bakuchiol against skin ageing and underline its potential as a holistic antiageing treatment approach. Résumé: Objectif: le vieillissement de la peau est un processus multifactoriel impliquant la formation de dérivés réactifs de l'oxygène, une inflammation consécutive qui entraîne une viabilité réduite des cellules du derme et de l'épiderme, et endommage la matrice extracellulaire. Pour être efficaces, les traitements dermocosmétiques devraient dans l'idéal traiter ces caractéristiques selon une approche holistique. Ici, nous avons déterminé le profil d'activité correspondant du bakuchiol, un méroterpène d'origine végétale, dans une série d'études in vitro, ex vivo et in vivo, et l'avons comparé au rétinol, qui est aujourd'hui considéré comme la référence parmi les cosmétiques anti‐âge topiques. Méthodes: la capacité antioxydante et la puissance du bakuchiol et du rétinol ont été analysées en mesurant la réduction du 2, 2‐diphényl‐1‐picrylhydrazyl (DPPH) selon sa décroissance par absorption et à l'aide d'une spectroscopie par résonance magnétique électronique, respectivement. Les effets sur la prostaglandine E2 (PGE2), le facteur inhibiteur de la migration (FIM) des macrophages, le facteur de croissance des fibroblastes 7 (FGF7), le collagène de type I et VII (COL1A1, COL7A1), les taux de fibronectine (FN), ainsi que la métabolisation du tétrazolium 1 soluble dans l'eau (WST‐1) ont été déterminés dans des fibroblastes dermiques humains. La régénération épidermique a été évaluée à l'aide d'un modèle de cicatrisation des plaies in vitro. Les taux de fibronectine ont été analysés ex vivo après un traitement avec une formulation contenant du bakuchiol, du rétinol ou un excipient à l'aide d'un liquide d'aspiration sous forme de vésicules. L'amélioration de l'état de la peau a été déterminée in vivo dans une étude de comparaison en hémiface après l'application de bakuchiol ou d'un excipient. Résultats: Contrairement au rétinol, le bakuchiol s'est avéré présenter une efficacité antioxydante élevée. Les taux de PGE2 et de FIM ont significativement diminué avec le bakuchiol et le rétinol. L'application de bakuchiol s'est accompagnée d'une augmentation significative des taux de protéine FGF7, mais pas celle de rétinol. Les taux de métabolisation du WST‐1 ont augmenté de façon significative avec le bakuchiol et le rétinol. L'application de bakuchiol et de rétinol a entraîné une augmentation significative des taux de protéines COL1A1, COL7A1 et fibronectine. Les plaies supplémentées en bakuchiol, mais pas en rétinol, ont montré une augmentation significative de la régénération épidermique. Sur le plan clinique, les zones traitées avec une formulation contenant du bakuchiol ont montré une augmentation statistiquement significative des taux de fibronectine après une application de 4 semaines par rapport aux zones non traitées et aux zones traitées avec un excipient. Conclusion: ces données fournissent des preuves de l'efficacité multidirectionnelle du bakuchiol contre les caractéristiques cellulaires du vieillissement de la peau. Son profil d'activité partage certaines caractéristiques communes avec le rétinol, mais démontre plusieurs effets biopositifs jusqu'alors inconnus dans nos études : la stimulation de la fibronectine, composante essentielle de la matrice extracellulaire, et une régénération épidermique et une cicatrisation accélérée des plaies.